COVID-19 and Farm Stands: Steps for Farm Stand Operators - Michelle Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS)
This new flyer, written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NCSU) and published by the UF/IFAS Food Science and Human Nutrition Department, provides information on best practices, communication with customers, and cleaning and disinfection for farm stand operators.